2017
DOI: 10.18632/oncotarget.17176
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of LAPTM4B, VEGF and survivin are correlated with tumor progression and poor prognosis in breast cancer patients

Abstract: ObjectiveThis study explored the relationships among the expression of LAPTM4B, VEGF, and survivin and clinicopathological characteristics and prognosis in breast cancer patients.MethodsThe expression of these three molecules in 110 stage I-III breast cancer patients with clinicopathological and follow-up data was detected via immunohistochemistry. Kaplan-Meier and Cox proportional hazard regression analyses were performed to assess the prognostic significance of these markers in breast cancer. Moreover, expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
1
36
1
1
Order By: Relevance
“…We tested LAPTM4B and miR‐132‐3p mRNA levels in breast cell lines by qPCR. Compared to MCF‐10A, MDA‐MB‐231 showed the lowest miR‐132‐3p expression level, and T47D showed the highest levels (Figure A); however, LAPTM4B expression was highest in MDA‐MB‐231 and lowest in T47D (Figure A), and the LAPTM4B protein level corresponded to its expression at the mRNA level in these breast cancer cells . In breast cancer tissues and matched adjacent normal tissues, LAPTM4B mRNA level was detected by TaqMan quantitative real‐time PCR.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We tested LAPTM4B and miR‐132‐3p mRNA levels in breast cell lines by qPCR. Compared to MCF‐10A, MDA‐MB‐231 showed the lowest miR‐132‐3p expression level, and T47D showed the highest levels (Figure A); however, LAPTM4B expression was highest in MDA‐MB‐231 and lowest in T47D (Figure A), and the LAPTM4B protein level corresponded to its expression at the mRNA level in these breast cancer cells . In breast cancer tissues and matched adjacent normal tissues, LAPTM4B mRNA level was detected by TaqMan quantitative real‐time PCR.…”
Section: Resultsmentioning
confidence: 98%
“…Compared to MCF-10A, MDA-MB-231 showed the lowest miR-132-3p expression level, and T47D showed the highest levels ( Figure 2A); however, LAPTM4B expression was highest in MDA-MB-231 and lowest in T47D ( Figure 4A), and the LAPTM4B protein level corresponded to its expression at the mRNA level in these breast cancer cells. 24 In breast cancer tissues and matched adjacent normal tissues, LAPTM4B mRNA level was detected by TaqMan quantitative real-time PCR. We found that LAPTM4B expression was significantly elevated in breast cancer specimens (8.790, 3.135-14.267, expressed as the median and quartile) ( Figure S1J).…”
Section: Correlation Between Laptm4b and Mir-132-3p Expression In Bmentioning
confidence: 99%
“…Immunohistochemistry analysis of AP4 (ab28512; Abcam, Cambridge, MA, USA), LAPTM4B (bs‐6542R Bioss, Boston, MA, USA) and Ki‐67 (ZA‐0502; ZSGB‐BIO, Beijing, China) was performed in HCC tissues according to a previous description (Li et al ., ). Stained tissue sections were evaluated separately by two pathologists without any knowledge of the clinical data.…”
Section: Methodsmentioning
confidence: 97%
“…BIRC5 was found to be expressed in fetal tissues and most human cancers, but absent in normal and differentiated tissues [28]. Its high expression in the primary cancer tend to associate with a poor prognosis for the patients [10,20,29]. However, the relation between high expression of BIRC5 and the prognosis of breast cancer is ambiguous, because other studies have reported it to be either irrelevant [30] or good prognosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, BIRC5 has been found to be overexpressed in a variety of human tumors, such as breast cancer [10,11], lung cancer [12], hepatocellular carcinoma [13], bladder cancer [14], colorectal cancer [15,16] and prostate cancer [17]. By now, a great majority of studies [18][19][20] have shown that BIRC5 was a pejorative prognostic marker in breast cancer, but the prognostic value of BIRC5 expression in breast cancer remains controversial.…”
Section: Introductionmentioning
confidence: 99%